Salivary alpha amylase in on-call from home fire and emergency service personnel. Issue 8 (November 2017) - Hall, Sarah J; Aisbett, Brad; Robertson, Samuel J; Ferguson, Sally A; Turner, Anne I
Abstract : The effect of working on-call from home on the sympatho-adrenal medullary system activity is currently unknown. This study had two aims, Aim 1: examine salivary alpha amylase awakening response (AAR) and diurnal salivary alpha amylase (sAA) profile in fire and emergency service workers who operate on-call from home following a night on-call with a call (NIGHT-CALL), a night on-call without a call (NO-CALL) and an off-call night (OFF-CALL), and Aim 2: explore whether there was an anticipatory effect of working on-call from home (ON) compared to when there was an off-call (OFF) on the diurnal sAA profile. Participants wore activity monitors, completed sleep and work diaries and collected seven saliva samples a day for one week. AAR area under the curve with respect to ground (AUCG ), AAR area under the curve with respect to increase (AUCI ), AAR reactivity, diurnal sAA slope, diurnal sAA AUCG and mean 12-h sAA concentrations were calculated. Separate generalised estimating equation models were constructed for each variable of interest for each aim. For Aim 1, there were no differences between NIGHT-CALL or NO-CALL and OFF-CALL for any response variable. For Aim 2, there was no difference between any response variable of interest when ON the following night compared to when OFF the following night ( n = 14). These findings suggest that there is no effect of working on-call from home on sAA, but should be interpreted with caution, as overnight data were not collected. Future research, using overnight heart rate monitoring, could help confirm these findings.